Principles and applications of clinical mass spectrometry : small molecules, peptides, and pathogens - Rifai, Nader; Horvath, Andrea R. (Andrea Rita); Wittwer, C. (Carl), 1955-; Hoofnagle, Andy N. (Elsevier, 2018)
Principles and Applications of Clinical Mass Spectrometry: Small Molecules, Peptides, and Pathogens, derived from the Sixth Edition of the bestselling Tietz Textbook of Clinical Chemistry and Molecular Diagnostics is a concise resource for the quick implementation of mass spectrometry methods in clinical laboratory work. Focusing on the practical use of these techniques, the book covers principles of chromatographic separations and types of mass spectrometers, along with sample preparations for analysis. Additional sections provide guidance on the use of the technology in the main applications in the clinical lab, including determination of small molecules and peptides, and in pathogen identification. Provides concrete examples on the main applications of this technologyAuthored, and edited, by the top experts in the United StatesDescribes the current capabilities of the LC- and MS-based analytical methods, along with the recipes for successful analytical work in the field